Editorial: The Future of Social Sciences - Bulent Tarman (Research in Social Sciences and Technology, 2017)
We have been facing with several challenges in all over the World. Global and local economies are facing threats as well as the increasing numbers of migrants that have not been seen for several decades. Resources are becoming scarcer and more expensive as we consume more. Technology and especially the internet and social networking are changing the way we work, interact and communicate. The question of "Why is the study of social sciences so critical to our future?" has been asked number of times in the past! To speak of the future of the social sciences is not an easy task especially nowadays where the dynamics of the World has been dramatically changing which brings lots of crisis with pain at every level from local to global.Â The name of this change has been called as the "New Order of the World" as some of the players lose their power and importance while new players comes in to show themselves and claim that they are also important and cannot be ignored!